Application of medical imaging in ovarian cancer: a bibliometric analysis from 2000 to 2022 - Leng, Yinping; Li, Shuhao; Zhu, Jianghua; Wang, Xiwen; Luo, Fengyuan; Wang, Yu; Gong, Lianggeng (Frontiers in Oncology, 2023)
Background Ovarian cancer (OC) is the most lethal tumor within the female reproductive system. Medical imaging plays a significant role in diagnosis and monitoring OC. This study aims to use bibliometric analysis to explore the current research hotspots and collaborative networks in the application of medical imaging in OC from 2000 to 2022. Methods A systematica search for medical imaging in OC was conducted on the Web of Science Core Collection on August 9, 2023. All reviews and articles published from January 2000 to December 2022 were downloaded, and an analysis of countries, institutions, journals, keywords, and collaborative networks was perfomed using CiteSpace and VOSviewer. Results A total of 5,958 publications were obtained, demonstrating a clear upward trend in annual publications over the study peroid. The USA led in productivity with 1,373 publications, and Harvard University emerged as the most prominent institution with 202 publications. Timmerman D was the most prolific contributor with 100 publications, and Gynecological Oncology led in the number of publications with 296. The top three keywords were “ovarian cancer” (1,256), “ultrasound” (725), and “diagnosis” (712). In addition, “pelvic masses” had the highest burst strength (25.5), followed by “magnetic resonance imaging (MRI)” (21.47). Recent emergent keywords such as “apoptosis”, “nanoparticles”, “features”, “accuracy”, and “human epididymal protein 4 (HE 4)” reflect research trends in this field and may become research hotspots in the future. Conclusions This study provides a comprehensive summary of the key contributions of OC imaging to field’s development over the past 23 years. Presently, primary areas of OC imaging research include MRI, targeted therapy of OC, novel biomarker (HE 4), and artificial intelligence. These areas are expected to influence future research endeavors in this field.